The Conservation challenges of Burkitu Community forest, Gasera District, Bale Robe, Ethiopia - Ahmed Abdela (Sustainability Science and Resources)
Aims:The study focused on the difficulties facing the Burkitu community forest in Southeast Ethiopia's Gasera District Bale Zone in terms of conservation. The Burkitu Community Forest got its name because the land is owned by a legally recognized group of individuals known as Burkitu. The woodland is 18.62 hectares in size and borders Ganda-Wotechimo and Gasera 01 on both sides.